Minimum Standards - Nussbaum, Tom.; California Community Colleges, Sacramento. Office of the Chancellor ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
The result of a comprehensive review by the Board of Governors of the California Community Colleges of the minimum standards entitling community college districts to receive state aid, this report provides background information, summarizes proposed changes, and offers the complete text of a revised set of regulations. Section I presents background on the Board's mandate to set regulations fixing minimum standards and to periodically investigate each community college to determine whether it has met these standards. This section also identifies themes that have emerged during the Board's 2-year investigation of the standards; summarizes the Educational Policy Committee's discussions; reviews proposed regulation changes; and proposes a process for future reviews. Section II, the bulk of the report, itemizes and provides commentary on the proposed regulations which include chapters on base levels of performance in instructional programs; qualifications and numbers of teaching staff; grading policies; facilities; counseling programs and staff; degrees and certificates; minimum class size; and approval of new colleges and centers. Appendices include proposals to reform accountability, criteria for minimum standards, a copy of the text of the minimum standards as adopted by the Board of Governors, and a policy for 1982-83 course cuts. (LL)
ERIC Note: Discussed as Agenda Item Number 6 at the Meeting of the Board of Governors of the California Community Colleges (March 10-11, 1983, Sacramento, CA). Final report in a series reviewing and revising the Board of Governors of the California Community Colleges' current minimum standards.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Standards; Accountability; Class Size; College Faculty; Community Colleges; Compliance (Legal); Counseling Services; Degrees (Academic); Educational Facilities; Eligibility; Grading; Policy Formation; State Aid; State Boards of Education; State Legislation; State Standards; Two Year Colleges; California; Opinion Papers; Legal/Legislative/Regulatory Materials